Handbook of sustainable development planning studies in modelling and decision support - Quaddus, M. A.; Siddique, Muhammed Abu B.; Edward Elgar Publishing (Cheltenham, U.K. ; Northhampton, Mass. : Edward Elgar, 2004)
This authoritative Handbook comprehensively examines the current status and future directions of model-based systems in decision support and their application to sustainable development planning.
pt. 1. Modelling for sustainable development -- pt. 2. Case studies -- pt. 3. Future directions.
Includes bibliographical references and index.
Keywords: Sustainable development -- Handbooks, manuals, etc; Decision making -- Handbooks, manuals, etc; Electronic books